Assessment of the impact of COVID-19 on transportation and its inter-linked sectors of Nepal - Singh, Dipendra Bahadur; Sah, Deepak Kumar (Journal of Engineering Issues and Solutions, 2021)
Nepal being a landlocked country is completely dependent on the roadways and airways for means of transportation however, the railway has not been started in Nepal to date. Transportation is interlinked with mobility and due to lockdown every sector related to mobility has been affected. Consequently, the aviation sector has been worst hit as airlines were prohibited to operate. The aviation industry of Nepal has foreseen significant decadence in the mobility of passengers and cargo (international and domestic) which has affected revenue generation. Similarly, the imposed lockdown has influenced the ongoing nation’s pride and the long-term investment projects which have been considered as a milestone in the infrastructural development of Nepal and those projects need to be reprogrammed and reprioritized. Moreover, the sharp decrease in import of petroleum products has decreased the revenue paid to the Indian Oil Corporation (IOC) which will help to reduce trade loss. The lockdown induced due to COVID-19 has also affected the agricultural sector as the supply chain has been disrupted due to travel restrictions. The overall Gross Domestic Product (GDP) that the transport and its inter-linked sector contribute has been reduced during lockdown than the preceding years. Identifying the paucity of research in the transportation sector of Nepal this paper is focused on the comprehensive study of the impact of the COVID-19 transportation sector along with its inter-connected areas.